[PP.16.14] OBSTRUCTIVE SLEEP APNEA BUT NOT RESISTANT HYPERTENSION INFLUENCES PLASMA FIBRIN CLOT PROPERTIES IN PATIENTS WITH HYPERTENSION AT HIGH CARDIOVASCULAR RISK. (September 2016) - Jozwik-Plebanek, K.; Prejbisz, A.; Pregowska-Chwala, B.; Michel-Rowicka, K.; Warchol-Celinska, E.; Kabat, M.; Bielen, P.; Sliwinski, P.; Januszewicz, A.; Undas, A.
Abstract : Objective: Both obstructive sleep apnea (OSA) and resistant hypertension (RHT) are related with high cardiovascular (CV) risk. Formation of dense and poorly lysable plasma fibrin clots is observed in clinical settings characterized by high CV risk. We investigated plasma fibrin clot properties in high-risk hypertensive patients with and without OSA or RHT but without clinically overt CV disease Design and method: We studied 88 hypertensive patients (64 M, 24F, mean age 48.6 ± 8.9years) at high CV risk (2007 ESH/ESC criteria) suspected of OSA. Patients with diagnosed atherosclerotic CV disease were excluded. Fibrin clot properties including clot permeability (Ks), clot lysis time (CLT), and turbidimetric parameters of clot formation (the lag phase of fibrin formation and maximum absorbency (δAbsmax) at 405 nm) were determined. All patients underwent PSG - the apnea/hypopnea index (AHI) > 15 events/h defined clinically important moderate-to-severe OSA. RHT was defined as uncontrolled HT despite using 3 antihypertensive drugs including diuretic. Patients were divided into 4 groups based on the presence of OSA or RHT: OSA-RHT-, OSA-RHT+, OSA+RHT−, OSA + RHT+ Results: There were no significant differences in gender, age and BMI between the groups. Patients in the OSA+ groups were characterized by lower Ks (5.88 ± 0.86 and 6.09 ± 0.96 vs 7.11 ± 0.90 and 7.58 ± 1.27 10 - 9 cm 2 ; p < 0.001) and by longer CLT (108.85 ± 13.88 and 102.12 ± 11.34 vs 96.46 ± 12.20 and 89.48 ± 15.67 min; p < 0.001 for OSA + RHT+ and OSA + RHT− vs OSA-RHT+ and OSA-RHT- groups respectively) as compared with the groups without OSA. In both OSA groups clots formed faster (lag phase, 41.39 ± 3.82 and 40.71 ± 4.81 vs 41.15 ± 4.20 and 44.60 ± 5.31 s; p = 0.018) and tended to had higher δAbsmax (0.86 ± 0, 05 and 0.86 ± 0.05 vs 0.85 ± 0.08 and 0.83 ± 0.07 min; p = 0.12 for OSA + RHT+ and OSA + RHT− vs OSA-RHT+ and OSA-RHT- groups respectively). Ks and CLT correlated with AHI but now with office BP and ambulatory BP levels Conclusions: In hypertensive patients at high CV risk, the presence of OSA but not of RHT was associated with unfavorable, prothrombotic changes in the structure and function of fibrin clots. The study may indicate the involvement of prothrombothic mechanism in which OSA may has an impact on CV risk